Expression of Indonesian People's Partiality in Protest News Uploads on Instagram @bbcindonesia - Rahma, Nurul Na'imahtul; Anindita, Maharani Laksmi; Ymaniyar, Nurul Apriani (Universitas Negeri Semarang, 2025)
This study aims to describe the form and function of expressive speech used by the public in responding to protest news discourse on Instagram (@bbcindonesia). This research is a qualitative descriptive research. The data source is from the Instagram comment column of @bbcindonesia, related to the news of the labor protest on August 28, 2025, in Jakarta. It found 30 samples of data taken from screenshots in the Instagram comment column @bbcindonesia. This study employs a theoretical approach based on pragmatic theory, specifically examining the function of speech actions. The study's results identified seven forms of expressive speech used by the community in responding to labor protest news discourse, namely expressive forms of sadness, concern, disappointment, swearing, enthusiasm, appreciation, and prayer and hope. Furthermore, in this study, expressive speech serves two primary functions: demonstrating solidarity and expressing the community's partiality. The results of the study show that the form of expressive speech aligns with its function as a means of solidarity and support, revealing a position of partisanship. Based on the results of this research, social media users tend to align with the community or the people themselves. This research is expected to enhance readers' knowledge, particularly in the pragmatic field related to the role of speech actions in the digital realm and their impact on the dynamics of people's language, especially in addressing social issues prevalent in Indonesia.